SCANSIONE LASER TERRESTRE E SENSORI GNSS-RTK PER LA CREAZIONE DI MODELLI SPAZIALI URBANI - Colombo, Luigi (GEOmedia, 2016)
The paper develops the topics for the metric documentation of urban environments and buildings through an experimental test regarding the thermal city of S. Pellegrino Terme, famous for its Art Noveau characters. The performed process of terrestrial laser survey, with a direct GNSS-RTK geo-referencing via a Reference Station Network, and the correspondent construction of a multi-scale photo-textured model of the site are described in detail.